Mural sobre las metas de los estudiantes en la educación superior en el muro izquierdo del hall principal del nuevo edificio administrativo de la Universidad Técnica de Machala, fundamentado en la técnica mixta al acrílico. - Sosoranga Pérez, José Ignacio (2013)
The importance of the MURAL theme on the goals of students in higher education, on the left wall of the main hall of the new administrative building of the technical university of MACHALA, foundation in the mixed technique to the acrylic is due to the knowledge and Skills acquired by the students of the BELLAS ARTES race of the Technical University of Machala, contributing to the cultural development of our provinces, as well as to the new administrative building of the university.